2017
DOI: 10.35188/unu-wider/2017/311-0
|View full text |Cite
|
Sign up to set email alerts
|

Biofuels technology: A look forward

Abstract: This paper assesses biofuels technology readiness and provides foresight to biofuels development in Southern Africa. Efficient conversion pathways, coupled with biomass from waste or high-yielding energy crops, reduces both the costs of biofuels production and the environmental impacts. Currently, most biofuels are more expensive than petroleum fuels and market uptake will be influenced by mandates and subsidies. Advanced biofuels promise greater efficiencies and carbon emission reductions at reduced cost, but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0
2

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 29 publications
1
13
0
2
Order By: Relevance
“…Eight advanced biofuel pathways to produce ethanol, renewable jet fuel (RJF), gasoline, diesel, methanol and dimethyl ether (DME) are considered. The conversion technologies are selected since they are already available or close to commercialization (Papadokonstantakis & City, 2017; Stafford et al, 2017). Not all lignocellulosic energy crops are directly suitable to be combined with all conversion technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Eight advanced biofuel pathways to produce ethanol, renewable jet fuel (RJF), gasoline, diesel, methanol and dimethyl ether (DME) are considered. The conversion technologies are selected since they are already available or close to commercialization (Papadokonstantakis & City, 2017; Stafford et al, 2017). Not all lignocellulosic energy crops are directly suitable to be combined with all conversion technologies.…”
Section: Methodsmentioning
confidence: 99%
“…Because a large data survey has not been carried out so far, the authors use average data on HTP archetypes identified by a literature review (cf. KIC InnoEnergy, 2015; Klemm et al, 2009; Reißmann et al, 2018; Stafford et al, 2017). It has to be mentioned that this preliminary calculation was just carried out to validate the model and the results are not reliable so far.…”
Section: Resultsmentioning
confidence: 99%
“…Other feedstocks such as JEDT 17,4 forest and other lignocellulosic residues are viable choices in areas where wood-based product manufacturing is common (Woiciechowski et al, 2016). Feedstock availability and prices are the key influential aspects for biofuels manufacturing in different regions of the world (Meyer et al, 2018;Melikoglu, 2016;Stafford et al, 2017). Therefore, a fixed biomass waste accumulation is essential to ensure a feasible deployment of a commercial biofuel plant for processing of organic wastes (Biofuels, 2018).…”
Section: Technical Feasibilitymentioning
confidence: 99%